Children's Attractiveness, Gender, and Race Biases: A Comparison of Their Strength and Generality. Issue 4 (22nd February 2014) - Rennels, Jennifer L.; Langlois, Judith H.
<x xml:space="preserve">Abstract</x> Although research suggests that facial attractiveness biases significantly affect social development and interactions, these biases are understudied in the developmental literature and are overlooked when designing interventions relative to gender and race. The authors, therefore, compared how much bias 3‐ to 11‐year‐olds (N = 102) displayed in the three domains. They also examined whether bias and flexibility (understanding that different social groups can possess similar attributes) were related across domains. Children's attractiveness biases, particularly for girl targets, were as strong as or stronger than gender or race biases. Flexibility, but not bias, was related across domains. Developmental scientists and policy makers should increase efforts toward understanding development of attractiveness biases and determine which methods of teaching flexibility are most successful at reducing bias across domains.